Model Pembentukan Peraturan Daerah Yang Ideal Dalam Penyelenggaraan Otonomi Daerah - Bunga, Marten (Jurnal Hukum & Pembangunan, 2019)
This study aims to analyze the model formation of regional regulations in the implementation of regional autonomy. This research method used is included in the type of normative legal research that uses secondary data obtained from library materials in the form of primary legal material. The results of the study indicate that regional regulations in the implementation of regional autonomy are a policy instrument in the implementation of the regional government. Establishment of regional regulations that are in accordance with the interests of the community must implement the principles of regional autonomy and the content of regional regulations must not conflict with higher laws and regulations. The ideal model of regional regulation in the implementation of regional autonomy is the principle of openness and community participation and the harmonization of laws and regulations that regulate it so that the regulations do not overlap.